AN EFFECT OF FINANCING TO DEPOSIT RATIO ON FINANCIAL PERFORMANCE OF ISLAMIC PEOPLE'S FINANCING BANKS IN NORTH SUMATRA - Nasution, Nina Andriany (Proceeding International Conference of Science Technology and Social Humanities, 2023)
The purpose of this study was to evaluate the Financial Performance of Islamic People's Financing Banks in North Sumatra. Specifically to analyze the effect of the Financing to Deposit Ratio (FDR) on Return On Equity (ROE). The research approach uses Quantitative with Panel Data Types for 2017 – 2021, Panel Data Multiple Linear Regression analysis techniques. The results of this study are: Financing to Deposit Ratio (FDR) has no partial effect on Return On Equity (ROE) at Islamic People's Financing Banks in North Sumatra.